Patterns of Comorbidity and In-Hospital Mortality in Older Patients With COVID-19 Infection - Mahmoud, Mona; Carmisciano, Luca; Tagliafico, Luca; Muzyka, Mariya; Rosa, Gianmarco; Signori, Alessio; Bassetti, Matteo; Nencioni, Alessio; Monacelli, Fiammetta, The GECOVID Study Group (Frontiers in Medicine, 2021)
Introduction Older adults have a higher susceptibility to the severe form of COVID-19 with increased all-cause mortality. This has been attributed to their multimorbidity and disability. However, it remains to be established which adults’ clinical features is associated with severe COVID-19 and with mortality, in order to have a correct prognosis and appropriate planning care. Starting from this background, here we aimed at identifying the chronic clinical conditions as well as the comorbidity clusters that were associated with in-hospital mortality in a cohort of octogenarian COVID-19 patients who wereadmitted atIRCCS Policlinico San Martino Hospital, Genoa, Italy, between January and April 2020. Methods This is a retrospective cohort study, including 219 consecutive old age patients aged 70 years and more and it is part of the GECOVID -19 collaborative group. During the study period upon hospital admission, demographics (age, sex) and underlying chronic medical conditions were recorded from the medical records at the time of COVID-19 diagnosis and before any antiviral and antibiotic treatments. The primary outcome measure was in hospital mortality. Results The vast majority of the patients (90%) were >80 years, had a mean age of 83 6.2 years and male accounted for 57.5% of the population. Hypertension and cardiovascular disease, along with dementia, cerebrovascular diseases and vascular diseases were the most prevalent clinical conditions. Multimorbidity multimorbidity was assessed with the Cumulative Illness Rating Scale. The risk of in-hospital mortality due to COVID-19 was higher for males, for older patients and for patients with dementia or cerebral-vascular disease. We clustered patients into three groups based on their comorbidity pattern: the “Metabolic-renal– cancer”, the“Neurocognitive and the“Unspecified” cluster. In both Neurocognitive and Metabolic-renal-cancer cluster a higher mortality was observed as compared to the Unspecified Cluster, independent from age and gender. Conclusion We clearly define patterns of comorbidity that accurately identify older adults who are at higher risk of death from COVID-19. These associations were found to be independent of chronological age and we suggest that they reflect impaired adaptative immune responses and inflammaging.